Black sails. The complete fourth season [videorecording (DVD)] - Ettlin, Lukas, 1975-; Sakharov, Alik, 1959-; Stephens, Toby, 1969-; New, Hannah; Arnold, Luke; Stevenson, Robert Louis, 1850-1894 (Lionsgate, 2017)
With the help of the daughter of a local kingpin, Captain Flint and his men attempt to fight off the British Navy.